Optimasi Komposisi Pelarut Gliserin dan Propilen Glikol terhadap Disolusi Tablet Meloksikam Metode Likuisolid Menggunakan Simplex Lattice Design (Optimization Composition of Glycerin and Propylene Glycol Solvent on Dissolution of Meloxycam Tablet with Li - Yudistirawati Khusna; Eka Deddy Irawan; Lusia Oktora Ruma Kumala Sari (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Meloxicam is Non Steroid Inflammation Drugs (NSAID) that inhibit cyclooxygenase-2 (COX-2). Meloxicam has poor solubility in water. The drug that has poor solubility, need to be modified to increase the solubility. The technique that can increase the solubility is liquisolid technique. The research aim was to develop tablet formulation of meloxicam by increasing the solubility using liquisolid method. This liquisolid tablet used combination of propylene glycol and glycerin as nonvolatile solvent to increase meloxicam release. The liquisolid tablets were evaluated for physical chemical characteristics e.g. homogeneity level, drug content uniformity, friability, hardness, disintegration time and in vitro drug release. Optimization composition of propylene glycol and glycerin used simplex lattice design method with nonvolatile solvent as a factor and dissolution efficiency (DE60) as response. The use of propylene glycol and glycerin will increase drug release. Optimum composition of propylene glycol and glycerin resulting optimum dissolution efficiency (DE60) between 78,88 – 88,48 % was propylene glycol with concentration of 0-15 mg and glycerin with concentration of 0-15 mg in 300 mg of tablet. Keyword: meloxicam, liquisolid, propylene glycol, glycerin, simplex lattice design